Analysis of Mathematical Communication Capabilities in Completing Problems in Matrix Materials Based on Solo Taxonomy - Sulis Setyowati; Yus Mochamad Cholily; Rizal Dian Azmi (MEJ (Mathematics Education Journal), 2020)
The purpose of this study is to describe the mathematical communication skills based on SOLO Taxonomy in students of class XI of Mathematics and Natural Sciences Muhammadiyah 3 Batu in solving problems on matrix material. This type of research is descriptive qualitative, where the subject is 17 students of class XI MIPA. The method of collecting research data uses test instruments. Based on the results of data analysis, it can be concluded thatas many as 4 students with very good mathematical communication skills criteria, 6 students with good mathematical communication skills criteria, 7 students with sufficient mathematical communication ability criteria and students. Whereas for students with written mathematical communication skills criteria lacking none. Students are in very good criteria, able to solve Unistructural - Relational level problems in SOLO Taxonomy. Meanwhile, students with good written mathematical communication skills are able to solve Unistructural level questions and Multistructural levels in SOLO Taxonomy. Then students with written mathematical communication ability criteria are quite capable of solving Unistructural level problems in SOLO Taxonomy.The average of written mathematical communication skills is in good criteria with the average value of written mathematical communication skills, namely 61.95, so that the average student is able to solve problems at a level Unistructural - Multistructural on SOLO Taxonomy.